PENGARUH JINGLE IKLAN MIZONE VERSI âLOVE TODAYâ DI TELEVISI TERHADAP BRAND IMAGE - Yunianto, Hasan (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2012)
Advertising is the tool of marketing and promotion. Television is the powerful media for advertising product. Jingle is strategy in advertising. Mizone used jingle â Love Todayâ in advertising for increase brand image. Brand Image is a set of association, usually organized in some way that has 4 dimension core product, actual product,augmented product, and image product. âLove Todayâ jingle in advertising is influences to Mizone brand image.